An investigation of the carbon-carbon bond rupture in fluoroethanes by RRKM theory - Aviyente, Viktorya. (Thesis (Ph.D.)- Bogazici University. Institute for Graduate Studies in Social Sciences, 1983., 1983)
In this dissertation, the thermal decompositions of ethane, 1,1,2,2-tetrafl uoroethane, pentafl uoroethane and hexafl uoroethane have been subjected to a theoretical treatment i n terms of the quantum statistical RRKM theory. The RRKM theory assumes that the activated molecule has a certain amount of vibrational energy spread among the various vibrational degrees of freedom of the molecule. Then the probability of one particular mode of vibration acquiring so much of this energy that the vibration leads to dissociation into fragments is calculated. The experimental results have shown that the first order rate constant for unimolecular reactions is not a true constant but declines at low pressures. The decline or "fall-off" in the first order rate constant with pressure is an important criterion of unimolecular reactions. The rate constants in this fall-off region as well as the rate constants at the experimental pressures and temperatures for the carboncarbon bond rupture for the above molecules have been evaluated. As already known, the major difficulty in this field is the determination of the configuration of the transition state . This is done in two different ways where two different models are suggested in the first one, the complex is considered as a decomposing diatomic molecule in which the atoms have the masses of the actual fragments. From this assumption follows the derivation of the length of the critical bond (Gorin Model ). In the second one, the critical configuration has a value o f the reaction coordinate such that the number of accessible internal states o f the molecule is minimized. The R+ value given by the criterion of minimum state density is less than the value given by the Gorin Model at the rotational barrier. Choosing the critical configuration at the rotational barrier gives an overestimate of the animolecular rate. In fact, the kuni values calculated for the first model are higher than those obtained for the second one. I n the evaluation of the rate constants, the centrifugal effects which reduce the activation energy for the reaction and the anharmonicity, resulting in a decreasing spacing between successive vibrational levels , are considered. As a result , the pressure at which the rate constant reaches one half it slimiting high pressure value increases with the number of fluorine atoms. This behaviour is in harmony with activation energies for the carbon-carbon bond scission, increasing with the number of fluorine atoms in the hydrocarbon.
Keywords: Moments of inertia.; Molecular theory.